Notes on the bryophyte flora and vegetation of the central and south-western Balkans. - Puglisi, Marta; Campisi, Patrizia; Lakušić, Dmitar; Surina, Boštjan; Di Pietro, Romeo; Privitera, Maria (Lazaroa, 2013)
A floristic and vegetation study was carried out in the mountains occurring at the boundary between Albania, Macedonia and Montenegro. The study area included Mt. Maja e Jezercës massif (Prokletije mts., SE Dinaric Alps) and Mt Korab(Šar-Pindos mountain range) in Macedonia. Several records for the bryological flora of Macedonia and Albania were reported. In particular Scapania cuspiduligera, Distichium inclinatum are new records for the Albanian flora. Moreover, the occurrence of some bryophytic and bryo-chormophytic associations belonging to the phytosociological classes Ctenidietea mollusci and Montio fontanae-Cardaminetea amarae was reported too.